Mentoring for learning : "Climbing the mountain" - Tillema, Harm; Van der Westhuizen, G. J.; Smith, Kari (SensePublishers, 2015)
No doubt, students appreciate the talks they have with their mentors but do they learn from it as well? Conversations can be comforting or confronting, but.